Chitosan- (Prunus avium) Gum Nanocapsules Loaded with Orange Peel Extract: Nanocapsules Loaded with Orange Peel Extract - alidee, Tahani; Habbal, Hoda; Karabet , Francois (Iraqi Journal of Pharmaceutical Sciences, 2023)
The orange peel extract (OE) is an additive material that has been used widely as a natural antioxidant source and bioactive compounds in Pharmaceutical and food sector. The poor stability and degradation of this extract were considered problems in the industry. New technologies have been introduced recently to prevent this degradation as encapsulation.In this work, chitosan (CS) and Prunus avium gum (PG) were proposed as promising based materials for encapsulation OE via ionic gelation method. The effect of different ratios of CS: PG and CS: OE on encapsulation efficiency (EE %) and the capsules size were investigated. The EE% of CS-PG was ranged from 60.63 to 87.06 % with a size range of 40 to 95nm according to Atomic Force Microscope (AFM) images. The formulation with the highest EE% was chosen to be characterized by FTIR, scanning electron microscope (SEM), and in vitro release study. The FTIR spectra confirm the cross-linking between the NH3+ group in CS and the negative functional group (-COO-) in PG. According to SEM micrographs, the capsules showed a spongy porous structure. The in vitro release study indicated that the release of OE from CS-PG matrix in the acidic and neutral medium was 55.15 and 52.67% respectively after incubation for 240 minutes. This study found that CS-PG can be used as an effective wall matrix for encapsulating OE and delivering it into the gastrointestinal system.